Methodological recommendations for the elaboration of the discussion of the clinical case report: Recomendaciones metodológicas para la elaboración de la discusión de un reporte de caso clínico - Pichardo Rodriguez, Rafael (2023)
Introduction: Case reports are a type of biomedical publication that allow us to share experiences regarding the etiology, diagnosis, therapeutics, and prognosis of anecdotal events that occur both in one and in several patients during clinical practice. Objective: to elaborate methodological recommendations for the elaboration of the discussion of a clinical case report. Methods: A narrative review of international guidelines and available evidence was carried out. Results: A total of 411,227 articles were located, finally selecting 10 narrative review articles. Discussion: The discussion is the most relevant section of the case report despite being considered by some journals as an optional contribution. We recommend for the elaboration of the discussion, to follow the following four steps: a) finding and comparison with the current evidence, b) justification of the causality of the findings, c) limitations and strengths in the management of the exposed case and d) clinical implications and prospects for the future. Conclusion: It is recommended to follow the four sequential steps for the elaboration of the discussion and to evaluate its impact on the scientific production in undergraduate and postgraduate students.